Microbiological quality and safety assessment in selected HACCP-certified dine-in and hospital facilities in Klang Valley, Malaysia - Subramaniam, Ramesh; Jambari, Nuzul Noorahya; Hao, Kuan Chee; Ungku Zainal Abidin, Ungku Fatimah; Mahmud@Ab Rashid, Nor Khaizura (Elsevier, 2023)
Food safety measures in food chain operations involving poultry meat are increasingly reliant on the hazard analysis and critical control point (HACCP) system as well as the effectiveness of its adoption in mitigating foodborne diseases. In this study, we evaluated the risk of microbiological contamination of poultry-based ready-to-eat (RTE) food through its preparation and subsequent handling at selected HACCP-certified dine-in food establishments and hospital catering facilities in Klang Valley, Malaysia. Samples obtained from 138 poultry-based RTE cook-served meals, 239 ready meals, 299 hand swabs, 510 food contacts, and 118 non-food contact surfaces were examined. The absence of Escherichia coli and Salmonella spp. in the RTE food samples showed a favorable trend in compliance with the Malaysian Food Act 1983 and Malaysian Veterinary Document Register Standard Operating Procedure (APTVM 16 (c):1/2011, Appendix 7) reference standards. The findings yielded by the microbiological assessments further revealed the non-conformance of coliforms in only 0.7 of the cook-served samples from the dine-in establishments. However, these percentages increased to 16.4 and 9.5 for coliforms and Staphylococcus aureus, respectively, in ready-food samples, whereas 6.5 and 5.7 were recorded in hospital facilities. In contrast, significant non-conformance with guidelines pertaining to food and non-food contact surfaces was noted for both dine-in establishments and hospital facilities. These results highlight the need for more stringent oversight of hygiene practices and process controls in all HACCP-certified facilities that prepare and serve food.